PERBANDINGAN KADAR KOLESTEROL HIGH DENSITY LIPOPROTEIN DARAH PADA WANITA OBES DAN NON OBES - Gani, Hanif B. S. (e-Biomedik, 2013)
Abstract: In general, obesity is associated with a decrease of blood HDL-cholesterol level and an increase of serum triglyceride level. In obese people, the triglyceride is deposited in the subcutaneous layer of the skin. This triglyceride plays an important role in the formation of VLDL and LDL-cholesterol in the liver which will be released into the blood. This was an observational study with a cross-sectional design. Samples were 22 obese female students and 22 non-obese female students of Faculty of Medicine, University of Sam Ratulangi Manado aged 18-22 years. The results showed that the mean HDL-cholesterol levels in obese females was 57.64 mg/dL, meanwhile of the non-obese females was 61.77 mg/dL. Albeit, the statistical analysis showed no significant difference between the HDL-cholesterol levels of obese and non-obese females (P-value 0.974). Conclusion: There was no significant difference between the HDL-cholesterol levels of obese females and non obese females. Keywords: HDL-cholesterol levels, females, obese, non obese Abstrak: Obesitas berhubungan dengan penurunan kadar kolesterol HDL darah dan peningkatan kadar serum trigliserida.3 Pada individu obes, trigliserida disimpan pada jaringan subkutan. Trigliserida itu merupakan bahan utama pembentukan VLDL dan LDL di hati yang akan dilepaskan ke dalam darah. Penelitian ini bersifat observasional dengan menggunakan cross-sectional design. Sampel penelitian terdiri dari 22 mahasiswi Fakultas Kedokteran Universitas Sam Ratulangi yang obes dan 22 mahasiswi yang non-obes. Hasil penelitian memperlihatkan bahwa rerata kadar kolesterol HDL pada sampel yang obes 57,64 mg/dL dan pada yang non-obes 61,77 mg/dL. Uji statistik memperlihatkan tidak terdapat perbedaan bermakna antara kadar kolesterol HDL darah pada wanita yang obes dan yang non-obes (P = 0,974). Simpulan: Tidak terdapat perbedaan bermakna antara kadar kolesterol HDL darah pada wanita obes dan wanita non-obes. Kata kunci: kadar kolestrol HDL, wanita, obes, non-obes.